Potential of Straw Compost plus Tithonia diversifolia And Rice Biochar to Improving NPK Nutrition And Growth of Rice (Oryza sativa L.) Paddy Soil - M. Lucky (Gontor AGROTECH Science Journal, 2020)
A one of the agricultural sector in the city of Padang. Kuranji District is expected to be able meet food needs in the fields of lowland rice cultivation. Fertilization with synthetic materials intensively causes the land to experience a decrease in fertility, which has an impact on rice production. One of the efforts to increase the potential of lowland rice cultivation in Kuranji Subdistrict to improve farming land by providing rice straw compost and biochar so as to reduce the use artificial fertilizer. The research objective was to study the effect of rice straw composts plus tithonia and biochar on the growth and nutrien uptake of lowland rice. The research as conducted in the TUI sub-district, Kuranji District in Padang City, using a randomized block design with 6 treatments and 3 replications, made of: 0% (compost and biochar); 100% compost; 75% compost and 25% biochar; 50% compost and 50% biochar; 25% compost and 75% biochar; 100% biochar. Soil and plant analysis was carried out at the soil laboratory at the Faculty of Agriculture, Andalas University, padang. The results showed that giving 25% compost and 75% biochar gave a good effect on the growth of lowland rice plants with production of 6.36 tons/ha; plant height 80.50 cm; total tillers 26.20 tillers, N uptake 21.13 kg/ha, P uptake 2.60 kg/ha, K uptake 183. 12 kg/ha.  * Korespondensi email: lucky25muhammad@gmail.comAlamat : Kampus Unand, Limau Manis, Kec. Pauh, Kota Padang, Sumatera Barat 25163